Bisegmentectomy 7–8 for Small-for-Size Remanant Liver for Cirrhotic Patients Under Right Hemi-hepatectomy With Hepatocellular Carcinoma: A Case-Matched Comparative Study - Wang, Xishu; Lei, Yongrong; Huan, Hongbo; Chen, Shu; Ma, Kuansheng; Feng, Kai; Lau, Wan Yee; Xia, Feng (Frontiers in Surgery, 2021)
AIM: To compare the short- and long-term treatment outcomes of bisegmentectomy 7-8 versus right hepatectomy for patients with hepatocellular carcinoma and cirrhosis. METHODS: Thirty six cirrhotic HCC patients with infiltration of right hepatic vein in segments 7–8 underwent bisegmentectomy 7–8 for small-for-size remanant liver under right hemi-hepatectomy. Its outcome was compared with a case-matched control group of cirrhotic HCC patients who underwent right hemihepatectomy during the study period. RESULTS: The study group consisted of 36 patients and the control group 36 patients selected from 1526 patients matched with age, tumor size, tumor location and Pugh-Child staging. There were no significant differences between the two groups in operative parameters and in perioperative main complications which included hemorrhage, bile leakage, ascites, pleural effusion and liver failure. The overall morbidity rate and morbidity rate classified according to Clavien’s classification were similar. There was no in-hospital mortality or 90-day post-operative mortality. The mean follow-up was 30 months and 32 months for the study group and control group, respectively. The disease free survival rate (DFS) for the study group was just significantly better than the control group. The median DFS was 24 months for the study group and 8 months for the control group (P=0.049). Meanwhile, the median cumulative overall survival was 35 months for the study group and 27 months for the control group (P=0.494). CONCLUSION: Bisegmentectomy 7–8 was safe and feasible for selected cirrhosis patients, and did not increase the perioperative risk and inferior long-term overall survival outcomes. It extended the indications for liver resection in patients with borderline volumes of future liver remnant for HCC cirrhotic liver.